1995
DOI: 10.1254/jjp.67.169
|View full text |Cite
|
Sign up to set email alerts
|

Effects of KCA-012 on Bone Metabolism in Organ Culture

Abstract: ABSTRACT-3,9-Dihydroxy-5H-benzofuro[3,2-c]quinoline-6-one (KCA-012), the chemical structure of which is closely similar to that of the phytoestrogen coumestrol, inhibited parathyroid hormone-, 1a,25-dihydroxyvitamin D3-and prostaglandin E2-induced bone resorption of cultured fetal rat bones. KCA-012 also increased the calcium content of 9-day chick embryonic femur cultured in vitro. KCA-012 did not show any estrogenic activity as determined by an increase in the uterine weight of ovariectomized rats, whereas c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…In fact, it was reported that daidzein and genistein increased estrogen-specific human alkaline phosphatase activity (1). Phytoestrogens also exhibited estrogenic actions on bone metabolism (2) and vasodilation (3). On the other hands, beneficial effects of phytoestrogens against cardiovascular disease and cancer have been reported (4,5).…”
mentioning
confidence: 99%
“…In fact, it was reported that daidzein and genistein increased estrogen-specific human alkaline phosphatase activity (1). Phytoestrogens also exhibited estrogenic actions on bone metabolism (2) and vasodilation (3). On the other hands, beneficial effects of phytoestrogens against cardiovascular disease and cancer have been reported (4,5).…”
mentioning
confidence: 99%